Development and characterization of microsatellite primers for Triops granarius (Branchiopoda: Notostraca) using MiSeq technology - Lina Ahmed (3342308) (2022)
Background Next-generation sequencing technology has allowed for the rapid development of microsatellites, neutral polymorphic markers that can be used for the analysis of population structure. Methods and Results In this study, we performed whole-genome sequencing using the Illumina MiSeq system and de novo assembly to design microsatellite primers for Triops granarius populations in Qatar. The developed microsatellites are suitable for future studies of genetic structuring among geographically isolated freshwater pools. A total of 23 different primer pairs produced typical microsatellite results, with each pair successfully amplified in up to 40 individuals. Only five of the loci produced a significant departure from Hardy-Weinberg equilibrium. Conclusions Some of the underlying mechanisms regarding the few loci that deviated from HWE may be further investigated to determine the source of deviation. As T. granarius is the most widely distributed species of the family, the development of these molecular markers would be useful for conducting population genetics and biogeographical studies broadly. Other Information Published in: Molecular Biology Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11033-022-07804-4